THE EFFECTIVENESS OF USING AUTHENTIC MATERIALS ON TEACHING SPEAKING FOR ELEVENTH GRADE STUDENTS’ OF ISLAMIC HIGH SCHOOL STUDENTS OF MU’ALLIMIN MUHAMMADIYAH YOGYAKARTA IN ACADEMIC YEAR 2013/2014 - Ilham Ilham (Universitas Muhammadiyah Mataram, 2016)
The objectives of this research is to find out whether the using authentic materials on teaching speaking is effective for eleventh grade students of Islamic High School of Mu’allimin Muhammadiyah Yogyakartain academic year 2013/2014 and whether there is any significance difference between students’ speaking ability taught by using authentic materials and thestudents’ speaking who taught by using created materials. This research is experimental research. The participants of the research were the eleventh grade students of Islamic High School of Mu’allimin Muhammadiyah Yogyakartain academic year 2013/2014. The research instrument used by the researcher was speaking test. The data in the research were mainly gathered through the use of pre-test and post-test. After the data were collected, the writer analyzed them. The researcher used SPSS16.0 to analyze the students’ speaking ability between the experimental group and the control group after the authentic materials was applied. Seeing from the finding of the research, it shows that there is a difference scores got by the students in theexperimental group and in the control group after the authentic material was applied. In the pre-test result, the mean of the experimental group was 58.85 and 58.94 for the control group. In post-test, after the authentic material was applied, the mean of the experimental group became 73.94 and 63.15 for the control group. It can be seen that the mean of the experimental group was higher than the control group in post-test. Seeing from the comparison of mean between the experimental group and the control group, it can be known that teaching speaking by using authentic material is effective. In order to find the answer of the hypothesis, certain statistics was used. The analysis of hypothesis testing was conducted using ANCOVA. From the computation, it was known that the significance of value was 0.029 < 0.05, then the null hypothesis (Ho) is rejected. Therefore, the hypothesis shows that there is a significance difference between students taught using authentic material and those taught without using created material is accepted